Utilization of MRI in Fetal Surgery - Wei Bian; Weizeng Zheng; Zesi Liu; Qiong Luo; Liqun Sun (iRADIOLOGY, 2025)
ABSTRACT Advances in fetal surgery techniques have enabled the treatment of certain congenital defects before birth. A critical area of focus is the role of perinatal imaging in optimizing prenatal interventions within the precision medicine framework. Magnetic resonance imaging (MRI) is emerging as an indispensable tool for guiding these intricate procedures with the potential to significantly enhance the standard of care and outcomes for affected fetuses. This review begins with an overview of the classification and indications for fetal surgical interventions. It then explores the detailed applications of prenatal MRI scanning and diagnostic techniques across various categories of fetal surgery. A key focus is how fetal MRI provides critical insights into specific lesion characteristics and tissue involvement, thereby aiding healthcare professionals in selecting the optimal surgical strategies for prenatal and postnatal interventions. Fetal MRI offers detailed visualizations that complement traditional ultrasound findings, enhancing the precision of radiological planning for fetal surgery. Finally, the review highlights how integration of fetal MRI into the decision‐making process enables healthcare providers to make well‐informed choices, ultimately improving the prognosis and outcomes for both the mother and fetus.